Facile synthesis of highly thermally stable TiO2 photocatalysts. (25th May 2017) - Mezni, Amine; Saber, Nesrine Ben; Ibrahim, Mohamed M.; El-Kemary, Maged; Aldalbahi, Ali; Feng, Peter; Samia Smiri, Leila; Altalhi, Tariq
Abstract : Synthesis of titanium dioxide (TiO2 ) nanoparticles by a new one-pot solvothermal process. Abstract : A new and facile method of synthesizing high-temperature stable titanium dioxide (TiO2 ) nanoparticles (NPs) is presented in this work. This novel approach allows the production of titanium dioxide nanoparticles owing to a modified solvothermal process that makes use of titanium(iv ) butoxide as a titanium precursor and Dimethyl Sulfoxide (DMSO) as a solvent. The structure and morphology of the TiO2 nanoparticles were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), energy dispersive X-ray spectrometry (EDX) and high-resolution transmission electron microscopy (HRTEM). Based on FTIR and TDA/TGA measurements, a proposed mechanism for the formation of TiO2 NPs in DMSO (without adding any other reagents) is discussed in this contribution. Optical absorption measurements showed that the TiO2 nanoparticles exhibited a UV significant absorption peak clearly blue-shifted with respect to that of bulk TiO2 . The results showed that monodisperse quasi-spherical TiO2 nanoparticles (with an average size of 11 nm) consisting of a pure anatase phase were formed. The titanium dioxide nanoparticles showed a high photocatalytic performance in the degradation of diuron pesticide (C9 H10 Cl2 N2 O) under illumination by UV light. The high crystalline quality, together with the easy synthesis process, makes TiO2 nanoparticles a promising candidate for many applications, such as optoelectronics and water photolysis for hydrogen production.